Less than one in five teenage women in Ethiopia know about emergency contraception - Tafere, Tesfahun Zemene; Teshale, Getachew; Jejaw, Melak; Demissie, Kaleb Assegid; Baffa, Lemlem Daniel; Geberu, Demiss Mulatu; Tiruneh, Misganaw Guadie; Hagos, Asebe (Frontiers in Global Women's Health, 2024)
BackgroundTeenage women's fertility health faces significant challenges from unintended pregnancies and unsafe abortions. Using an emergency contraception within a defined time period could prevent unintended pregnancy and its damaging consequences, like unintended childbirth and unsafe abortion. Despite it being an appropriate contraception, the knowledge of teenage women about emergency contraception is lower among women in developing countries. Therefore, this study aimed to examine the magnitude of emergency contraception knowledge and its associated factors among teenage women in Ethiopia.MethodsData for this study was obtained from the recent Demographic and Health Surveys. A total weighted sample of 3,381 teenage reproductive women were included. The significant associated factors with emergency contraception knowledge among teenage reproductive women were determined by fitting a multilevel mixed-effect binary logistic regression model. Finally, Adjusted Odds Ratio (AOR) with a 95% confidence interval and a P value of less than 0.05 was used to declare statistical significance.ResultsIn Ethiopia, the magnitude of teenage women who knew about emergency contraception was 19.47% (95%CI: 18.17, 20.84). Age 17 years (AOR = 1.76, 95%CI, 1.24, 2.48) and age 19 years (AOR = 2.18, 95%CI, 1.47, 3.22), primary education level (AOR = 2.76, 95%CI, 1.60, 4.76), secondary and above educational level (AOR = 4.70, 95%CI, 2.62, 8.44), being protestant followers (AOR = 0.63, 95%CI, 0.45, 0.87), being muslim followers (AOR = 0.68, 95%CI, 0.49, 0.93), media exposure (AOR = 3.36, 95%CI, 2.59, 4.34), rural residence (AOR = 0.45; 95%CI: 0.22, 0.86), and high community level education (AOR = 140, 95%CI: 1.32, 2.00) were factors significantly associated with knowledge of emergency contraception among teenage women.ConclusionsThis finding concluded that less than one in five teenage women knew about emergency contraception in Ethiopia. The knowledge of emergency contraception among teenage women in Ethiopia was substantially associated with women's age, education level, religion, media exposure, residency and community-level education. Hence, there is a need to implement comprehensive awareness programs and promotion of emergency contraception as a way of curbing cases of unintended pregnancies among teenage women. Government and non-governmental organizations should design targeted educational initiatives and media campaigns to improve emergency contraception knowledge among young teenagers, women with lower educational backgrounds, and rural teenagers.